PENGUATAN KOMPETENSI, LINGKUNGAN KERJA DAN PENDIDIKAN DALAM MENINGKATKAN KINERJA KARYAWAN BPJS KETENAGAKERJAAN CABANG GORONTALO - Hendrayanto, Hendrayanto; Kamidin, Masruhi (JURNAL MANAJEMEN BISNIS, 2018)
This study was conducted with the aim of knowing and analyzing the dominant variables influencing employee performance at the BPJS Work Office in the Gorontalo Branch Office. This study uses data collection techniques through questionnaires and literature studies with data analysis techniques for quality testing (validity and reliability test), classical assumption test (normality test, multicollinearity test and heterokeddasticity test), multiple linear regression analysis and hypothesis testing (partial test and test simultaneously). Based on the results of regression testing, the results show that the dominant variable that influences employee performance at BPJS Employment in the Branch Office of Gorontalo is the work environment, the reason being that it has the largest beta value when compared to competency and education variables.